PEMBERDAYAAN SANTRI DALAM SIMULASI SIAGA BENCANA TSUNAMI DI MADRASAH TSANAWIYAH NURUL HUDA KABUPATEN ACEH BARAT - Fatimah Siti Zahara; Miftahul Jannah; Deki Farman; Raboni Alfitrah; Sahrul Ramadhan; Mohamad Gazali (Jurnal Marine Kreatif, 2021)
Indonesia is a country with high-risk potential for various types of disasters because Indonesia is located between three large tectonic plates of the earth, namely the Eurasian Plate, the Indo-Australian Plate and the Pacific Plate.  West Aceh  Regency  is  one  of  the  districts  included  in  the  level  of  high  hazard classification for tectonic earthquakes that can cause Tsunamis.  The stage of empowerment community includes conducting the survey, the coordinating with principal of MTSS Nurul Huda, socialication of tsunami disaster and the simulation of tsunami disaster alert. In conducting the community empowerment, the students are enthusiasms to follow the socialization and the simulation of tsunami disaster aler.